IFN-γ and IL-10 Regulation in the MuLV-Infected MAIDS Model - Roses, Stephanie (My University, 2013)
Those infected with Human Immunodeficiency Virus (HIV) classically progress to Acquired Immune Deficiency Syndrome (AIDS), an illness typified by an increase in opportunistic infections ranging from influenza to tuberculosis to several kinds of cancer. Since its identification in 1982, 24 million people worldwide have died as a result of AIDS. Not everyone infected with HIV progress to AIDS at the same rate, most falling into two groups: rapid progressors and long-term nonprogressors (LTNPs). These LTNPs are an exciting and important area of research on methods to inhibit progression to AIDS. The murine AIDS (MAIDS) model used in this experiment consisted of the C57BL/6 mouse infected with murine leukemia virus (MuLV) to induce AIDS-like symptoms. The infection in MAIDS model mice typically mirrors human rapid progression in AIDS. These mice were compared to a BALB/c mice who, when infected with MuLV, more closely parallel a LTNP AIDS response. Previous research has suggested a link between early expression of the immunosuppressant cytokine Interleukin-10 (IL-10) in MAIDS-susceptible C57BL/6 mice after three and seven days of infection with MuLV and the rapid progression AIDS response shown in these mice. C57BL/6 mice showed reduced levels of IL-10 and an accompanying high viral count after three and seven days. In this experiment, we hypothesized that, like in the previous research, BALB/c mice would exhibit low levels of IL-10 compared to C57BL/6 mice after both were infected with MuLV for 3.5 days. To investigate whether higher expression of inflammation typical of a successful antiviral response complements low expression of IL-10 and vice versa, the inflammatory cytokine Interferon-γ (IFN-γ) was hypothesized to have an inverse relationship with IL-10. This experiment imitated the methods of previous Stranford lab research, using the same animal models and Enzyme-Linked Immunoabsorbent Assays (ELISAs). BALB/c MAIDS-resistant mice were expected to express low levels of IL-10 and high levels of IFN-γ after 3.5 days of infection and C57BL/6 MAIDS-susceptible mice were expected to express high levels of IL-10 and low levels of IFN-γ after 3.5 days of infection. As in previous research, both mouse models showed similarly low expression levels of both IL-10 and IFN-γ before infection. Contrary to previous research and these hypotheses, however, the only significant difference was a rise in IL-10 concentrations between BALB/c pre-infection mice and day 3.5 post-infection mice. No significant differences between infection observation point or mouse strain were found in IFN-γ analysis. With a lower viral titer achieved this year than in previous research and adjustments to cytokine concentrations made for protein concentration in samples for the first time in this experiment, these results do not support the findings of previous research and may open an avenue of low-titer research in MuLV/MAIDS and eventually HIV/AIDS.
Keywords: Biology; HIV; AIDS; MuLV; immunology; Biochemistry